Prevalence and correlation of sarcopenia with Alzheimer's disease: A systematic review and meta-analysis. - Chen Su; Sen Zhang; Qiandan Zheng; Jie Miao; Junhong Guo (PLoS ONE)
Background Sarcopenia, which is defined by a decline in skeletal muscle mass and strength associated with aging, is common among older individuals and presents considerable health dangers. Alzheimer's disease (AD) is a prevalent degenerative brain condition linked to a decrease in cognitive function. The intersection of these conditions remains underexplored. The goal of this systematic review and meta-analysis was to establish the frequency of sarcopenia in individuals with AD and investigate the relationship between sarcopenia and AD. Methods We performed an extensive review of literature databases, including PubMed, Embase, Web of Science, and the Cochrane Library, through April 2024. The inclusion criteria included studies that provided data on the frequency of sarcopenia in patients with AD or that examined the odds ratios (ORs) associated with these comorbidities. R Studio (4.3.1) was utilized for conducting the statistical analyses. Results A total of 27 studies, comprising 3902 AD patients were included. In patients with AD, the combined occurrence of sarcopenia was 33.9%, with a confidence interval (CI) of 95%, ranging from 27.6% to 40.2%. Sarcopenia was found in 31.2% (95% CI: 0.223-0.402) and 41.9% (95% CI: 0.321-0.516) of patients with mild and moderate AD, respectively. The OR for the association between AD and sarcopenia was 2.670 (95% CI: 1.566-4.555), suggesting a robust correlation. Conclusion Sarcopenia is highly prevalent in AD patients, highlighting the need for integrated care approaches to address both cognitive and physical health issues. Further research is needed to elucidate the pathophysiological links between AD and sarcopenia.